Development of adhesion between two concretes during concrete hardening - Halicka, Anna; Franczak, Dominika (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
The main factor influencing the bearing capacity in composite members is bond strength between concretes, because only effective joint between substrate and overlay ensure their full structural cooperation. One of the component of bond strength is adhesion between concretes. In the current paper, development of bond strength between jointed concretes in different ages, is discussed. The results of the experimental tests of tension bond strength development between two concretes, are presented.